Effects of temperature at constant air dew point on leaf carboxylation efficiency and CO 2 compensation point of different leaf types - Weber, J. A.; Tenhunen, J. D.; Lange, O. L. (Planta, 1985)
The effect of temperature on photosyn- thesis at constant water-vapor pressure in the air was investigated using two sclerophyll species, Ar- butus unedo and Quercus suber, and one meso- phytic species, Spinacia oleracea. Photosynthesis and transpiration were measured over a range of temperatures, 20-39 ~ C. The external concentra- tion of CO 2 was varied from 340 ~tbar to near CO 2 compensation. The initial slope (carboxylation effi- ciency, CE) of the photosynthetic response to inter- cellular CO 2 concentration, the CO 2 compensation point (/-), and the extrapolated rate of CO 2 re- leased into COa-free air (Ri) were calculated. At an external CO 2 concentration of 320-340 labar CO2, photosynthesis decreased with temperature in all species. The effect of temperature on F was similar in all species. While CE in S. oleracea changed little with temperature, CE decreased by 50% in Q. suber as temperature increased from 25 to 34 ~ C. Arbutus unedo also exhibited a de- crease in CE at higher temperatures but not as marked as Q. suber. The absolute value of Ri in- creased with temperature in S. oleracea, while changing little or decreasing in the sclerophylls. Variations in F and Ri of the sclerophyll species are not consistent with greater increase of respira- tion with temperature in the light in these species compared with S. oleracea.
Keywords: Carboxylation efficiency; Compensation point (CO2); Photosynthesis (temperature-humidity); Sclerophyll; Transpiration